(untitled) (Al-Academy, 2023)
The elements of theater formation that fall within the spatial experience of the scenography of the show, which the directors work in in the imaginary theater, are important and have an aesthetic, intellectual and cognitive dimension, working to highlight reality in an aesthetic image surrounding space and space. And its relationship to the distinct, multiple and variable spaces above the stage, to produce theatrical signals and endless meanings through the possibility of infinite reconfiguration of the theater’s space and its public and private space through the distribution of a group of blocks within the scenic image.I dealt with in the first chapter (the methodological framework), which includes the research problem identified by the researcher, the importance of the research and the aim of the research, then the researcher determined the limits of the research and defined the terms and then defined them procedurally. The researcher also presented in the second chapter (the theoretical framework) two main topics: "Knowing scenography historically", the second topic is "the meaning of scenography in theatrical performance", and in the third topic "the aesthetics of scenography in the theatrical performance system", and then reviewed the most prominent indicators that resulted from the theoretical framework. The third chapter deals with the research procedures, and determines the research sample, the play "Red Carpet", scripted and directed by Dr. Jabbar Judy. And then in the fourth chapter, the results and conclusions were extracted, and recommendations and suggestions were made, in order to finally fix the references and sources of the research